Proteolytic enzyme and inhibitor levels in reindeer (Rangifer tarandus tarandus L.) vs. bovine longissimus muscle, as they relate to ageing rate and response - Barnier, V. M.H.; Wiklund, E.; van Dijk, A.; Smulders, F. J.M.; Malmfors, G. (Rangifer, 1999)
Eight reindeer bulls (age 1.5 years) and six Friesian bulls (age 1.5 years) were included in the study for comparison of tenderness. The reindeer were slaughtered at a commercial reindeer slaughter plant in northern Sweden and the Friesian bulls at a commercial slaughter plant in The Netherlands. Samples for determination of calpain/calpastatin activity were taken from the M. longtssimus (LO) within 1 h post mortem (p.m.), and at various times p.m. pH and temperature were registered in LO; ultimate pH values were measured at 24 h p.m. for beef and at 35 h p.m. for reindeer. At day 1 p.m., samples of LO from both carcass sides were excised, divided in two parts, vacuum packaged and stored at 0-2 °C. One part of each muscle was randomly sampled at 1, 3, 7 and 14 days p.m. for determination of shear force, proteolytic enzyme activity, myofibrillar protein degradation, collagen content and heat solubility. pH and temperature fall was faster in reindeer than in beef. Collagen content in reindeer muscle was found to be low but collagen was 4 times less soluble as compared with beef. Reindeer LO was found to be extremely tender, at 3 days p.m. shear force values were only 2-3 kg/cm2 (8-12 kg/cm2 for beef LO). In reindeer meat, the jJ.-calpain levels dropped to about 55% within 3 days. Troponin T and 30 kDa values were not related to changes in tenderness in reindeer meat. Cathepsin activities in reindeer were up to ten times higher than in beef. As in beef, cathepsin B+L levels in reindeer increased during storage, which is probably associated with a decrease in cystatin-like inhibitor levels.